Educational Tourism Management Based On Experiential Learning In Pulutan Tourism Village - Hermawan, Yudan; Tohani, Entoh; Wibawa, Lutfi; Septiantoko, Rico; Bekti Utami, Rita (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
Pulutan Tourism Village develops and empowers the community, one of the innovative models developed is educational tourism based on experiential learning. The purpose of this study is to a) describe the management strategy in developing Pulutan Tourism based on experiential learning b) supporting and inhibiting factors. This study used an exploratory case study with the sample selected using a purposive sampling method. Data was collected through in-depth interviews, observation, and documentation. The Analysis Interactive Model from Miles and Huberman is used to analyze the results, namely: data collection, data reduction, data presentation, and drawing conclusions or verification. Research result; a) the strategy is carried out starting from identifying the potential and objectives of Wista Education, designing educational programs, involving local communities, training and education, infrastructure and facilities, promotion, and evaluation and improvement. b) Supporting factors; Strategic Location, Relevant Education Program and Local Community Involvement. While the inhibiting factors namely; Lack of Resources and Funds, Lack of Education and Training and Climate Change.Keywords: development, tourism, tourist village, educational tour, experiential learning